Analisis Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Kota Bandung Pasca Pandemi Covid 19 - Dora, Yenny Maya; Saefudin, Nugraha; Sari, Oktora Yogi; Sakti, Intan Widuri; Sudrajat, Asep; Sumantri, Dadan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The contribution of MSMEs is quite large for the national economy because, with a large number of existing MSMEs, more jobs will be created for people who need jobs and become the biggest contributor to Domestic Product Value (Gross). Therefore, Micro, Small, and Medium Enterprises (MSMEs) need special attention in this sector. The research was conducted to analyze the development of MSME entrepreneurs in the city of Bandung after the Covid 19 pandemic for MSME entrepreneurs. The number of MSME entrepreneurs who were sampled was 110 respondents from several types of businesses. The type of research conducted was survey research with descriptive and verification data analysis methods. The results of the study partially show that the Entrepreneurial Character variable has a positive influence on MSME business development, while the Business Capital variable does not have a positive effect on business development. And the marketing strategy variable partially has a positive effect on business development. Business capital that does not have a positive effect on business development does not mean that MSME players do not need venture capital in developing their businesses. Even though MSME entrepreneurs have sufficient capital without strong and positive characteristics of MSME entrepreneurs, business development will not work While the simultaneous test results obtained results of Entrepreneurial Characteristics, Business Capital and Marketing Strategy jointly affect Business Development. This illustrates that with strong entrepreneurial characteristics and supported by the availability of business capital and marketing strategies that are in accordance with market conditions, business development carried out by MSME entrepreneurs will certainly run well Keywords: Entrepreneurial Characteristics, Business Capital, and Business Development.